Evidence of an allostatic response by intestinal tissues following induction of joint inflammation - Meghan M. Moran; Jun Li; Quan Shen; Sheona P. Drummond; Caroline M. Milner; Anthony J. Day; Ankur Naqib; D. Rick Sumner; Anna Plaas (PLoS ONE, 2026)
Disrupted intestinal epithelial barrier function has been proposed to be integral to rheumatoid arthritis (RA) progression and pathogenesis. To further define the molecular pathways in synovial inflammation and the response of the intestinal tissues, we have used a rat model of mono-joint inflammatory arthritis, induced by intra-articular injection of Complete Freund’s adjuvant (CFA). The predominant inflammatory response of a single injection of the adjuvant into the knee joint resulted in rapid and reproducible formation of a fibrotic myeloid-infiltrated synovial pannus. Our aim was to determine how intestinal tissues, including the proximal and distal ileum and distal colon, responded to inflammatory changes in the synovium in a temporally coordinated manner by comparing their transcriptomic landscapes using RNASeq analyses. We confirmed the timeline of joint inflammation by knee joint swelling measurement, increased synovial fluid levels of bikunin (a component of both the acute phase protein pre-alpha-inhibitor and inter-alpha-inhibitor) and demonstrated a self-correcting response of trabecular and cortical bone to the CFA challenge. Intestine-specific responses were monitored by 16S microbiome amplicon sequencing, histopathology for mucus layer integrity, and immune cell immunohistochemistry. We present data that shows the intestinal tissue displays an allostatic response to the acute joint inflammation and was region specific. The ileum primarily responded with increased mucus secretion and silencing of T-cell specific pathways, whereas the colon showed a transient upregulation of macrophages, with a broader suppression of immune related and metabolic pathway related transcripts. Interestingly, many neuropathways were activated early but then suppressed later in both the ileum and colon. There were only insignificant changes in the fecal microbiome composition in ileum or colon post-CFA administration. In summary, our data show for the first time a suppression of intestinal inflammatory and immune responses following the induction of joint inflammation and only minimal and transient changes in the microbiome. The results help clarify the molecular responses of intestinal tissues to inflammatory stresses that accompany the pathogenesis of inflammatory joint diseases.